Collectie Philippe Dotremont. - Fierens, Paul; Stedelijk Van Abbemuseum, Eindhoven (Amsterdam : Stedelijk Museum Amsterdam, 1954)
Appel, Karel ; Baumeister, Willi ; Bazaine, Jean ; Bertrand, Gaston ; Bissière, Roger ; Bonnard, Pierre ; Bonnet, Anne ; Braque, Georges ; Brusselmans, Jean ; Calder, Alexander ; Cézanne, Paul ; Delahaut, Jo ; Deyrolle, Jean ; Dufy, Raoul ; Ensor, James ; Estève, Maurice ; Hartung, Hans ; Heerbrandt, Henri ; Herbin, Auguste ; Istrati, Alexandre ; Jacobsen, Robert ; Kandinsky, Wassily ; Klee, Paul ; Lapicque, Charles ; Laurencin, Marie ; Leger, Fernand ; Van Lint, Louis ; Magnelli, Alberto ; Magritte, René ; Matisse, Henri ; Mendelson, Marc ; Miro, Joan ; Mortensen, Richard ; Mortier, Antoine ; Permeke, Constant ; Pevsner, Antoine ; Picasso, Pablo ; Pignon, Edouard ; Poliakoff, Serge ; Rousseau, Henri ; Schneider, Gérard ; Singier, Gustave ; Soulages, Pierre ; Tal-Coat, Pierre ; de Toulouse-Lautrec, Henri ; Tytgat, Edgard ; Ubac, Raoul ; Vantongerloo, Georges ; Vasarely, Victor ; Villon, Jacques
geboortedata kunstenaars
Collectie Philippe Dotremont, Stedelijk Museum Amsterdam, Stedelijk Van Abbemuseum, Eindhoven, voorjaar 1954
Nederlands & Frans
boek